War- and famine-related excess mortality among civilians in the Netherlands, 1944–1945 - Peter Ekamper; Govert E. Bijwaard; Frans W.A. van Poppel; L.H. Lumey (Journal of Maps, 2020)
National estimates exist for war- and famine-related deaths in the Netherlands during the last stages of World War II, but no such estimates are available at the local level. To fill this information gap, this article aims at mapping and visualizing the timing of war- and famine-related excess mortality by municipality among the civilian population within the Netherlands. We use mortality statistics at the level of municipalities because these are the smallest administrative units for which this information is available. We use a seasonally adjusted mortality model combined with a difference-in-difference approach to estimate the number of excess deaths in the period between January 1944 and July 1945 separately for each Dutch municipality.